Nick of time - Bell, Ted (New York St. Martin's Griffin, 2008)
With the help of Lord Hawke, whose children have been taken by the evil pirate Captain Billy Blood, young Nick McIver uses a time machine to rescue the two children as well as change the course of events in two time periods, the Napoleonic Wars and World War II
Php 399.00
Donated by Gorriceta-Rojo family 12.11.18
Keywords: Boys -- Channel Islands -- Fiction; World War, 1939-1945 -- Channel Islands -- Fiction; Pirates 4v Fiction; Kidnapping -- Fiction; Rescues -- Fiction